2020
DOI: 10.2147/ott.s279951
|View full text |Cite|
|
Sign up to set email alerts
|

<p>CCNB1 Expedites the Progression of Cervical Squamous Cell Carcinoma via the Regulation by FOXM1</p>

Abstract: Background: Cervical squamous cell carcinoma (CSCC) is responsible for 80-85% of cervical cancer. Cyclin B1 (CCNB1) represents a hub gene during the development of cervical cancer. However, the oncogenic role of CCNB1 in CSCC remains unclear. Our study aims to explore the mechanism underlying CCNB1 regulation on cell cycle progression in CSCC cells. Methods: First, we analyzed differentially expressed genes from CSCC dataset GSE63678 and conducted gene function enrichment analysis. Subsequently, CCNB1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
“…BRCA1 enhanced the sensitivity of cervical squamous cell carcinoma (CSCC) patients to cisplatin-based CCRT by up-regulating STAT1 to activate the JAK/STAT pathway [ 50 ]. CCNB1 played vital roles in the progression of CC through different signaling pathways [ 17 , 18 , 26 , 46 , 51 ]. CDK1 contributed to the occurrence and development of CSCC [ 18 , 23 , 25 , 26 , 27 , 40 , 41 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were 6 common KEGG pathways in the CIN-CC group ( p < 0.01), namely, the adipocytokine signaling pathway, small cell lung cancer ( ITGA6 [ 25 ], PIAS3 , and LAMC2 [ 26 ]), pathways in cancer, the Toll-like receptor signaling pathway, graft versus host disease, and the TGF-beta signaling pathway [ 27 ]. There were 9 common KEGG pathways in the N-CC group ( p < 0.01), namely, the cell cycle ( PCNA , CDC25B , MCM3 , MCM5 , CDC6 [ 28 ], GSK3B , MCM6 , CHEK2 , PKMYT1 , CDC20 [ 29 ], PTTG1 , SMAD3 , CCNB1 [ 30 ], RBL1 , CDC7 [ 23 ], WEE1 , CDK2 [ 31 ], CCNA2 , and TTK ), nucleotide excision repair, the Toll-like receptor signaling pathway, prion diseases, spliceosome, DNA replication, proteasome, colorectal cancer, and pancreatic cancer. Moreover, GSEA showed that DNA mismatch repair (N-CIN), small cell lung cancer (CIN-CC), and the cell cycle (N-CC) were the most significantly enriched pathways ( P < 0.01, FDR < 0.05), and snapshots of the enrichment analysis are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have showed that the overexpression of CCNB1 is common in many cancers, such as adrenocortical carcinoma, cervical carcinoma, stomach cancer, non-small cell lung cancer, and rhabdomyosarcoma. 1216 A study showed that CCNB1 could promote the proliferation of pituitary adenomas and stimulate epithelial-to-mesenchymal transition. 17 In pancreatic cancer, CCNB1 silencing promotes cell senescence and suppresses cell proliferation by activating the p53 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%